2019
DOI: 10.1186/s13756-019-0650-z
|View full text |Cite
|
Sign up to set email alerts
|

Unidirectional animal-to-human transmission of methicillin-resistant Staphylococcus aureus ST398 in pig farming; evidence from a surveillance study in southern Italy

Abstract: BackgroundLivestock-associated methicillin-resistant Staphylococcus aureus (MRSA) belonging to clonal complex 398 is recognized as an occupational hazard for workers employed in intensive animal husbandry, especially in the swine-breeding chain. In this study, we compared the prevalence and epidemiological type of MRSA isolates from swine and farm workers in a large area of southern Italy.MethodsBetween January and March 2018, 88 workers from 32 farms where we had previously performed a survey for MRSA coloniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 39 publications
2
36
0
3
Order By: Relevance
“…According to the EFSA report on antimicrobial monitoring on MRSA, the main route of transmission of LA-MRSA into the population is direct contact with animals, e.g., at abattoir level, and then dissemination [ 61 ]. In line with this, the study carried out by Pirolo et al [ 62 ] involving pig farm workers demonstrated that 21.6% of the workers were colonised by livestock-associated MRSA (LA-MRSA) and that this colonisation was significantly higher if direct animal–human contact occurred. Additionally, Cuny et al [ 63 ] detected a 30% antibiotic multiresistance to penicillins, tetracyclines and macrolides in ST398 MRSA isolated from humans in contact with farm animals, a fact that poses a therapeutic challenge if infection occurs.…”
Section: Discussionmentioning
confidence: 75%
“…According to the EFSA report on antimicrobial monitoring on MRSA, the main route of transmission of LA-MRSA into the population is direct contact with animals, e.g., at abattoir level, and then dissemination [ 61 ]. In line with this, the study carried out by Pirolo et al [ 62 ] involving pig farm workers demonstrated that 21.6% of the workers were colonised by livestock-associated MRSA (LA-MRSA) and that this colonisation was significantly higher if direct animal–human contact occurred. Additionally, Cuny et al [ 63 ] detected a 30% antibiotic multiresistance to penicillins, tetracyclines and macrolides in ST398 MRSA isolated from humans in contact with farm animals, a fact that poses a therapeutic challenge if infection occurs.…”
Section: Discussionmentioning
confidence: 75%
“…A substantial number of isolates carried the PVL gene, corroborating a study conducted on S. aureus isolated from backyard-raised pigs and pig workers in Nigeria, with 27% of isolates harbouring PVL [ 65 ]. However, although PVL has been associated with necrotising pneumonia and joint infection in humans, its role in pigs is not thoroughly investigated; hence, the current findings should be interpreted with caution [ 66 ], as its presence does not necessarily imply diseased animals.…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial resistant bacteria originating in an animal can be transmitted to humans through the environment, food products, and/or by direct contact [ 8 ]. Similar strains of resistant bacteria are found in food animals and humans suggesting the bacterial transmission from animals to humans [ 21 ]. Plasmid-mediated resistance in E. coli , Salmonella and Klebsiella to colistin, a last line group of antimicrobial drug, is reported in both food animals and humans in countries from North America, Europe, Africa and Asia [ 17 ].…”
Section: Main Textmentioning
confidence: 92%